Incontinencia Urinaria y su afectación en la Calidad de Vida, en centros geriátricos de la provincia de Imbabura: Urinary incontinence and its effect on quality of life, in geriatric centers of the Province of Imbabura (La U Investiga, 2020)
Urinary incontinence (UI) according to the International Incontinence Society (ICS) is defined as any involuntary loss of urine; This condition does not imply a vital risk for the patient, but it significantly deteriorates the quality of life of those who suffer from it, since it reduces their self-esteem and autonomy, being considered an important medical and social problem. The objective was to determine the prevalence of UI and its effect on the quality of life of those who suffer from it. The methodology of this study is descriptive, not experimental, cross-sectional, with a qualitative-quantitative and epidemiological approach. The study population was 299 elderly women who belong to Geriatric centers in the Province of Imbabura. Among the instruments, the IU International Consultation on Incontinence ICIQ-SF test and I-QOL quality of life test were applied. Through the results, a prevalence of urinary incontinence of 57%. Was determined, the most frequent being the stress urinary incontinence with 41%. The quality of life was found to be affected in 96% of the women with UI, the sub-scale of avoid and limit behavior being the most affected.
Keywords: Urinary incontinence; Quality of life; Prevalence